2020
DOI: 10.1177/1352458520923958
|View full text |Cite
|
Sign up to set email alerts
|

Functional electrical stimulation for foot drop in people with multiple sclerosis: The relevance and importance of addressing quality of movement

Abstract: Impaired mobility is common in people with multiple sclerosis (MS). Changes in gait have different causes and require individualised gait rehabilitation. A common and often early cause of mobility impairment is footdrop, inability to lift the foot during the swing phase of gait, with increased risk of falls, effortful walking and fatigue. Using literature review, we have characterised published data on footdrop treatment in MS, specifically functional electrical stimulation (FES) to better understand the repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…A recent narrative review of the use of FES, by Smith et al 56 also concluded that future studies should investigate the impact of FES on a wider range of Patient Reported Outcomes (PROMS) but also use qualitative approaches to capture users' opinions and observed changes in addition to changes in quantitative outcomes. A qualitative study by Wilkinson et al 57 of 20 people less than 6 months post‐stroke explored ‘valued personal’ benefits of FES not measured by walking speed and identified factors such as spontaneity, freedom, automaticity (ability to walk without thinking about it), and self‐determination as important benefits.…”
Section: Discussionmentioning
confidence: 99%
“…A recent narrative review of the use of FES, by Smith et al 56 also concluded that future studies should investigate the impact of FES on a wider range of Patient Reported Outcomes (PROMS) but also use qualitative approaches to capture users' opinions and observed changes in addition to changes in quantitative outcomes. A qualitative study by Wilkinson et al 57 of 20 people less than 6 months post‐stroke explored ‘valued personal’ benefits of FES not measured by walking speed and identified factors such as spontaneity, freedom, automaticity (ability to walk without thinking about it), and self‐determination as important benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary results of the application of an assistive robotic glove at home indicated that both the orthotic and the therapeutic use of the glove resulted in comparable gains in UL function. 13 Furthermore, it has been suggested that the orthotic application of FES might play a role in patients’ motivation, 21 which could positively influence motor learning. 22 …”
Section: Introductionmentioning
confidence: 99%
“…The functional impairment of major clinical relevance for people with multiple sclerosis (pwMS) is gait disturbance, which is one of the principal reasons for a slow walking speed and it is characterized by muscle weakness, fatigue and an altered gait biomechanics [2,3]. Among the altered biomechanics parameters, there is a limited ankle dorsiflexion during the swing phase of gait due to weakness in the tibialis anterior that leads to foot drop [2,4]. Foot drop has important clinical effects since it is accompanied by an increased risk of falls, decreased level of activity, and constraints on quality of life [4].…”
Section: Introductionmentioning
confidence: 99%
“…Among the altered biomechanics parameters, there is a limited ankle dorsiflexion during the swing phase of gait due to weakness in the tibialis anterior that leads to foot drop [2,4]. Foot drop has important clinical effects since it is accompanied by an increased risk of falls, decreased level of activity, and constraints on quality of life [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation